2004
DOI: 10.1590/s0103-50532004000600011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of self-assembled thiols monolayers on gold surface by electrochemical impedance spectroscopy

Abstract: Tióis de cadeias carbônicas com tamanhos diferentes e contendo grupo terminal COOH foram usados para formar monocamadas auto-organizadas sobre a superfície de eletrodos de ouro. A transferência de elétrons do par Fe(CN) 6 3-/4-para o eletrodo foi estudada em diferentes pH usandose as técnicas de voltametria cíclica (CV) e de espectroscopia de impedância eletroquímica (EIS). Mudanças no pH da solução resultaram em variações na carga do grupo terminal das monocamadas auto-organizadas e, conseqüentemente, em alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 21 publications
2
57
0
1
Order By: Relevance
“…After seeding the 3T3 fibroblasts and PC12 cells on the MEA, the changes of the total impedance, including resistance and reactance between the cell-microelectrode-medium interfaces, were recorded at the same measurement condition once every day for 7 consecutive days. Research has simplified this electrode-SAMs interface through the application of a parallel model where the electrode impedance is presumably composed of electrode resistance (R e ) and shunt capacitance (C e ) from SAMs modification (Chidsey and Loiacono 1990;Mendes et al 2004;Chou et al 2003). In our study, additional resistance (R s ) and capacitance (C s ) of the sealing gap, which interpreted the interface between cells and electrodes (Rutten et al 2001;Buitenweg et al 2002), had to be recruited after cells culturing on the electrodes.…”
Section: Impedance Evaluation Of Surface-modified Microelectrodesmentioning
confidence: 86%
See 1 more Smart Citation
“…After seeding the 3T3 fibroblasts and PC12 cells on the MEA, the changes of the total impedance, including resistance and reactance between the cell-microelectrode-medium interfaces, were recorded at the same measurement condition once every day for 7 consecutive days. Research has simplified this electrode-SAMs interface through the application of a parallel model where the electrode impedance is presumably composed of electrode resistance (R e ) and shunt capacitance (C e ) from SAMs modification (Chidsey and Loiacono 1990;Mendes et al 2004;Chou et al 2003). In our study, additional resistance (R s ) and capacitance (C s ) of the sealing gap, which interpreted the interface between cells and electrodes (Rutten et al 2001;Buitenweg et al 2002), had to be recruited after cells culturing on the electrodes.…”
Section: Impedance Evaluation Of Surface-modified Microelectrodesmentioning
confidence: 86%
“…5(d)) also indicated that PDL molecules were in a well-ordered distribution, linked through MUA with some pinholes. Pinholes were regarded as defects in a thiol monolayer in another study (Mendes et al 2004). However, pinholes might allow molecules and ions that flow from the medium or electrolyte to reach the electrode surface.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of penetration of the probe through the monolayer is controlled by the chemical and physical characteristics of the molecule probe and defect sites of the SAM. As in basic media the hexacyanoferrate is negatively charged, it should have a repulsive force towards the deprotonated À COO -of 3 MPA SAM [53], mainly if it is dense and well-ordered. For this reason hexacyanoferrate(II/III) was chosen as the probe molecule.…”
Section: Effect Of Electrode Pretreatment On Thiol Monolayer Self-assmentioning
confidence: 99%
“…Although electrochemical immunosensors can reach low detection limits, the electrical and, even more, the electrochemical properties of self-assembled monolayers have not been the subject of many studies. Mendes et al (2004) studied the characterisation of self-assembled thiol monolayers on gold surfaces by electrochemical impedance spectroscopy [11]. Despite previous studies on the topic, it is not yet well understood how the applied potential affects the self-assembled monolayers' properties.…”
Section: Introductionmentioning
confidence: 99%
“…Despite previous studies on the topic, it is not yet well understood how the applied potential affects the self-assembled monolayers' properties. In general, monolayers are known to be unstable under the effect of applied potentials because of their reductive and oxidative desorption [11].…”
Section: Introductionmentioning
confidence: 99%